Effects of an inulin fiber diet on the gut microbiome, colon, and inflammatory biomarkers in aged mice - Noah T. Hutchinson; Selena S. Wang; Laurie A. Rund; Maria Elisa Caetano-Silva; Jacob M. Allen; Rodney W. Johnson; Jeffrey A. Woods (Experimental Gerontology, 2023)
Due to the increasing human life expectancy and limited supply of healthcare resources, strategies to promote healthy aging and reduce associated functional deficits are of public health importance. The gut microbiota, which remodels with age, has been identified as a significant contributor to the aging process that is modifiable by diet. Since prebiotic dietary components such as inulin have been shown to impart positive benefits with regards to aging, this study used C57Bl6 mice to investigate whether 8 weeks on a 2.5 % inulin enhanced AIN-93M 1 % cellulose diet could offset age-associated changes in gut microbiome composition and markers of colon health and systemic inflammation in comparison to a AIN 93M 1 % cellulose diet with 0 % inulin. Our results demonstrated that, in both age groups, dietary inulin significantly increased production of butyrate in the cecum and induced changes in the community structure of the gut microbiome but did not significantly affect systemic inflammation or other markers of gastrointestinal health. Aged mice had different and less diverse microbiomes when compared to adult mice and were less sensitive to inulin-induced microbiome community shifts, evidenced by longitudinal differences in differentially abundant taxa and beta diversity. In aged mice, inulin restored potentially beneficial taxa including Bifidobacterium and key butyrate producing genera (e.g. Faecalibaculum). Despite inducing notable taxonomic changes, however, the 2.5 % inulin diet reduced alpha diversity in both age groups and failed to reduce overall community compositional differences between age groups. In conclusion, a 2.5 % inulin enhanced diet altered gut microbiome α and β diversity, composition, and butyrate production in both adult and aged mice, with more potent effects on β diversity and greater number of taxa significantly altered in adult mice. However, significant benefits in age-associated changes in systemic inflammation or intestinal outcomes were not detected.